2023
DOI: 10.3389/fnagi.2023.1107372
|View full text |Cite
|
Sign up to set email alerts
|

Health disparities in aging: Improving dementia care for Black women

Abstract: In the United States, 80% of surveyed Black patients report experiencing barriers to healthcare for Alzheimer’s disease and related dementias (ADRD), delaying the time-sensitive treatment of a progressive neurodegenerative disease. According to the National Institute on Aging, Black study participants are 35% less likely to be given a diagnosis of ADRD than white participants, despite being twice as likely to suffer from ADRD than their white counterparts. Prior analysis of prevalence for sex, race, and ethnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…We observed that Black patients with AD were more likely to be hospitalized during the COVID-19 pandemic. This finding is consistent with prior reports that race was a risk factor in acute care utilization [ 31 , 39 ]. For example, compared to White patients, Black patients with AD had increased odds of Emergency Department (ED) visits and hospitalizations [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…We observed that Black patients with AD were more likely to be hospitalized during the COVID-19 pandemic. This finding is consistent with prior reports that race was a risk factor in acute care utilization [ 31 , 39 ]. For example, compared to White patients, Black patients with AD had increased odds of Emergency Department (ED) visits and hospitalizations [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…It may enhance or possibly replace immunotherapy in some who are so afflicted. Relief would flow to women (LC/T1DM87/other autoimmune diseases), especially those of color (AA [136], psoriasis [137], vitiligo [138], AD [139], T2DM [140]).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the critical need to consider the role of sex and gender, as well as the use of exogenous hormones, throughout the spectrum of ADRDs, from prevention to detection and treatment. Similarly, studies did not consider race and ethnicity, even though Black women are at the highest risk for ADRD (56). These will be important demographic data points for future studies to consider.…”
Section: Discussionmentioning
confidence: 99%